Epidemiology of Gall Stone Diseases among Patients attending Surgical Department of a Tertiary Care Hospital in Nepal - Chaudhary, Sanjay (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Gallstone disease (GSD) is a chronic disease that consumes a lot of economic and medical resources. It not only affects patients’ life quality, but also is associated with the potential risks of the development of consequences of gallstone diseases. Therefore, the study is aimed to investigate the epidemiology and risk factors of gall stone diseases among patients attending tertiary care centre in Nepal.Material and Methods: A cross sectional study was conducted among patients attending surgical department of Janaki Medical College Teaching Hospital (JMCTH) over a period of one year from January 2019 to December 2019. Chi-square test was applied to show the association between the two groups. P-value < 0.05 was considered statistically significant.Results: In a total of 148 patients, 69.59% had mixed gallstone, 17.57% had cholesterol stone and 12.84% had pigment gallstone. Types of gallstone was found significant for age group (p=0.006), gender (p=0.027) and presence of diabetes (p=0.003) but insignificant with presence of hypertension (p=0.992).Conclusion: Age of the patients, gender and presence of diabetes were found significant for the all types of gall stone. Further large scale research need to be conducted.